Analysis Applicants' Characteristics and Universities of Ministry of Science' Situation in Employment New Faculty Members - hadi mosadegh; Reza Jafari Harandi (Allameh Tabataba'i University Press, 2017)
The aim of this research was to a survey the Situation of applicants and universities in employment the faculty member. The methods which has been used are library study, a follow up in the ministry of science research and technology, and interview with experts. The population investigated were the invited applicants and all universities under the Ministry of Science.The results; First, in the last ten years a number of faculty member have advanced, but the gap between the application rate and the permit to employ individuals ,in the last three years, has increased, while the number of employment permits has decreased. Second:a student teacher ratio in proportion to the universities under the Ministry of Science, no change , high ratio increase in University of Peyame Noor and high ratio decrease in the private institutions. Third: most need demand rate applications is for University of Tarbiyat Modares, and least for university of Khalige Fars. Forth: most need demand rate applications to join a chemistry field, and least is for field of Computer engineering. Fifth: the average marks of male applicants was better than female. And a number of executives experience and researches work were opposite. Sixth:All applicants were Iranian nationals.